Finally 'changing lenses'?: state-level determinants of restorative justice laws - Sliva, Shannon M. (The prison journal, 2018)
This article presents a mixed methods study exploring a legislative trend toward the use of restorative justice practices in correctional settings. Results indicate that the percentage of Black residents in a state, the percentage of female legislators in a state legislature, and a state’s incarceration rates are predictive of more supportive restorative justice policy adoptions at the state level, while controlling for other explanations. The study weighs political and economic considerations in the adoption of policies with the potential to reduce overincarceration and suggests that at least some contemporary criminal justice police making is motivated by changing constructions of justice.